Estructura diamétrica y carbono almacenado en las especies comerciales de un bosque de terraza baja de la comunidad nativa Uranias, distrito de Ramón Castilla, Loreto. 2022 - Granados López, Cecilia Elizabeth (2022)
The diameter structure and the carbon stored in the commercial species of a low terrace forest in the district of Ramón Castilla, Loreto, Peru were quantified. The forest census data of the commercial species of the operational plan (PO)1 of the cutting plots (PC) 1 and (PC) 2 of the forest concession contract 16-LOR-MAY/CON-MAD-2019-038 were evaluated. for timber purposes. The distribution of the number of trees by diameter class reports 1.36 trees/ha (1,339 trees). The species Maquira coriacea (0.90 trees/ha, 886 trees), Eschweilera bracteosa (0.24 trees/ha, 233 trees) and Pouteria hispida (0,10 trees, 100 trees) contain a greater number of trees; while Ceiba pentandra (0,007 trees, seven trees, Ocotea javitensis (0.004 trees/ha, four trees) and Ceiba samauma (0,003 trees/ha, three trees) report fewer trees. The carbon stored is 5,00 tC/ ha (4905,12 tC) The species Maquira coriacea (3,03 tC/ha, 2972,50 tC), Eschweilera bracteosa (1,25 tC/ha, 1226,80 tC), Pouteria hispida (0,40 tC/ ha, 396,99 tC) and Calycophyllum spruceanum (0,23 tC/ha, 227,64 tC) present higher value, while Ceiba pentandra (0,04 tC/ha, 42,15 tC), Vochysia vismiifolia (0, 02 tC/ha, 19,57 tC), Ceiba samauma (0,01 tC/ha, 9,87 tC) and Ocotea javitensis (0,01 tC/ha, 9,61 tC), show lower value. correlation (r=0,978) between the diametric structure, the biomass and the carbon stored for a significance of α = 0,01.